Programas de aceleração corporativos: motivações para implementação sob a ótica da ambidestria organizacional - Torres, Ariana Alves (2019)
Corporate accelerators are gaining attention as a key element to foster innovation, as many organizations are experimenting different ways to set up and manage their acceleration initiatives. However, the reasoning for implementing corporate acceleration programs is not fully understood. This study aims to fill this gap by identifying the corporate acceleration programs and the main reasons private companies in Brazil are creating and executing them, from the perspective of organizational ambidexterity. Therefore, a qualitative and descriptive approach with multiple case studies was developed; data was collected through documentary research and semi-structured interviews, and was analyzed according to Gioia, Corley and Hamilton’s recommendation. The results suggest that managers use corporate acceleration as a tool to employ exploration and exploitation. Exploration is promoted through the limited duration of the programs; internal mentors; physical structure apart from the corporation and differentiated environment; program’s culture; changes in corporate team’s behavior; quest to generate new businesses and trends created by startups. Exploitation is revealed as such programs can induce organizational changes and new working methods; adjust and improve corporate processes and the programs themselves; corporates select startups that relate to their core businesses and carry out incremental innovation. The results highlight how the corporate executives’ engagement, support and sponsorship are important for the program’s success.